Intermediate Algebra: Connecting Concepts through Application

Published by Brooks Cole
ISBN 10: 0-53449-636-9
ISBN 13: 978-0-53449-636-4

Chapter 8 - Radical Functions - 8.3 Multiplying and Dividing Radicals - 8.3 Exercises - Page 642: 25


$15-5\sqrt {15}+3\sqrt 6-3\sqrt {10}$

Work Step by Step

$(5+\sqrt 6)(3-\sqrt {15})$ =$5(3-\sqrt {15})+\sqrt 6(3-\sqrt {15})$ =$15-5\sqrt {15}+3\sqrt 6-(\sqrt 6\sqrt {15})$ =$15-5\sqrt {15}+3\sqrt 6-\sqrt {6\times15}$ =$15-5\sqrt {15}+3\sqrt 6-\sqrt {90}$ =$15-5\sqrt {15}+3\sqrt 6-\sqrt {9\times10}$ =$15-5\sqrt {15}+3\sqrt 6-(\sqrt 9\times\sqrt {10})$ =$15-5\sqrt {15}+3\sqrt 6-3\sqrt {10}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.